Is the white-ivory assay of Drosophila melanogaster a useful tool in genetic toxicology? - Ferreiro, J.A.; Consuegra, S.; Sierra, L.M.; Comendador, M.A. (Environmental and Molecular Mutagenesis, 1997)
The white-ivory assay of Drosophila is based on the detection of reversions to wild-type phenotype of ommatidia with the white-ivory mutation. A tandem quadruplication of this gene is used in order to increase the reversion probability. Although the exact mechanism implicated in reversion is not known, revertant spots are believed to arise as a consequence of intrachromosmal recombination or related phenomena. Since the white-ivory assay has not been broadly used, the number of chemicals tested until now is still limited. In this work, we have assayed 25 chemicals belonging to several chemical groups, i.e., crosslinking agents, DNA-topoisomerase inhibitors, antimetabolites/nucleotide pool inhibitors, cyclic-adduct inducers, halogenated hydrocarbons, bulky-adduct inducers, intercalating agents, oxidative damage inducers, and a multiple damage inducer, to validate this test. Cross-linking agents, halogenated hydrocarbons, and the multiple damage inducer, dounomycin, were positive. On the contrary, the three antimetabolites/nucleotide pool inhibitors tested were negative. The other chemical groups showed disparate results, since some chemicals were positive, whereas others were negative in each group. A comparison with the results obtained in the w/ w+ and mwh/flr3 assays shows that the wi assay detects a more restricted spectrum of damages than those, although, with respect to carcinogenicity, its sensitivity (0.76, with the 62 chemicals tested until now) is similar to that estimated for the mentioned somatic assays. The conclusion of this work, then, is that the wi assay is not recommended as a general screening test, because the background reversion frequencies show a high variability among solvents, the range of lesion-recognition is lower than in the w/ w+ and mwh/flr3 SMARTs, and the mechanism implicated in the white-ivory reversion is poorly understood.